Regional tissue oxygen saturation during minimal enteral feeding is associated with the subsequent feeding intolerance in very preterm infants - Jianyun Chen; Xi Fan; Shanshan He; Zhiying Lin; Zhiwen Su; Fan Wu (Scientific Reports)
Abstract Feeding intolerance (FI) is a common clinical problem in very preterm infants (VPIs) and it increases the risk for adverse outcomes. The value of regional tissue oxygen saturation in predicting FI remains unclear. A total of 57 VPIs were involved in this study, and the regional splanchnic and cerebral tissue oxygen saturation during minimal enteral feeding in the first 3 days after birth was monitored and analyzed. Compared with the feeding tolerance (FT) group, the FI group had a smaller gestational age, lower birth weight, and higher rate of maternal hypertensive disorders in pregnancy. Even more, the FI group had lower regional splanchnic tissue oxygen saturation and lower splanchnic-cerebral oxygenation ratio (SCOR) at the 1st hour and 2nd hour after feeding on the 3rd postnatal day than the FT group (P < 0.05). Multivariate logistic regression analysis showed that increased gestational age and elevated SCOR at the 2nd hour after feeding on the 3rd postnatal day reduced the risk for FI (P < 0.05). The areas under the curve (AUCs) of gestational age, SCOR at the 2nd hour after feeding on the 3rd postnatal day and their combination in predicting FT were 0.745 (95%CI 0.616 ~ 0.874), 0.756 (95%CI 0.628 ~ 0.883) and 0.820 (95%CI 0.710 ~ 0.929), respectively.